Fortuitous Le Fort Osteotomy in an Interpersonal Assault- A Case Report. - Satyabrata Pattnaik1 , Sanchari Sinha Roy2 , Harsh Mohan Pathak1 , Subrat Padhiary3 , Soumya Kanti R (Institute of Medico-legal Publications Pvt Ltd, 2020)
Violence is one of the primary sources of facial injury. It forms a big part of emergency care and trauma anddiffers from each because of the physical, psychosocial and economic relations. Trauma from pointed armshappens less frequently affecting the head and neck region, most commonly affecting males. Facial injury:83 percent comprises of bone fracture, 66 percent of lacerations & 53 percent comprises of hematomas.